Toxoplasma gondii immunoglobulin G in paired infant-and-mother sera - Ayling Sanjaya; Nurhayati Masloman; Rocky Wilar; Josef Tuda (Paediatrica Indonesiana, 2009)
Background  Toxoplasmosis  is  a worldwide zoonotic diseasecaused  by  Toxoplasma  gondii.  Congenital toxoplasmosis (CT)is  the  result  of  vertical transmission  during  pregnancy  thatmay cause pathologic effects  on  the newborn such  as  classicaltriad  of  congenital toxoplasmosis.  Newborn  humans  are  notimmunologically  competent  and the infant must be protected  by passive lgG antibodies  that  are selectively transported across the placenta during development.  We  studied the transfer  of  passive lgG from the  mother  to developing infant using blood specimen taken from the infant within one  month  of  birth.Objective  To  determine the seropositivity  of  lgG to  T.  gondii  in paired sera  of  infants and mothers.Methods  A cross sectional study was carried  out  on  50 pairedsera  of  infants  of  less  than  one  month  of  age and their mothers. The  study was carried  out  between November 2007 and January 2008  at  Prof.  R.  D.  Kandou Hospital in Manado.  T.  gondii  lgG was detected using the Latex Agglutination method.  The  seropositivity ofT.  gondii  lgG was analyzed descriptively.Results  A total  of  28 mothers from 50 infant-mother pairs wereseropositive for  T.  gondii  IgG.  Of  the 28 seropositive mothers, 22  of their paired infants were seropositive.  The  remaining six seropositive mothers  had  infants  that  were  not  seropositive for T.  gondii.Conclusions  The  identification  of  seropositive lgG for  T.  gondii in infants less  than  one  months  age indicates  that  the lgGs in infants are mostly derived from their mothers.  CT  must be considered  and  further  examinations  are needed.